X-Ray Scattering of Soft Matter - Stribeck, Norbert; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Applications of X-ray scattering to soft matter have advanced considerably within recent years, both conceptually and technically – mature high-power X-ray sources, synchrotrons and rotating anodes, as well as high-speed detectors have become readily available. High-quality time-resolved experiments on polymer structure now can be performed with ease, a major advancement due to the genuine power of the scattering method. This manual summarizes the analytical power of modern X-ray scattering in the field of soft matter. Description of simple tools that can elucidate the mechanisms of structure evolution in the studied materials is followed by a step-by-step guide and breakdown of the more advanced methods. Data analysis based on clear, unequivocal results is rendered simple and straightforward – with a stress on the carefully planning of the experiments and adequate recording of all required data. To this end, this book serves as a useful ready-reference guide.
Polydispersity and Heterogeneity -- General Background -- Typical Problems for Analysis by X-Ray Scattering -- Experimental Overview -- Acquisition of Synchrotron Beamtime -- It’s Beamtime, Phil: A Guide to Collect a Complete Set of Data -- Pre-evaluation of Scattering Data -- Interpretation of Scattering Patterns -- High but Imperfect Orientation -- Orientation Growing from the Isotropic State -- Fitting Models to Data.                                                                                          .
Keywords: Polymers .; Condensed matter; Materials science; Amorphous substances; Complex fluids; Physical chemistry; Polymer Sciences; Condensed Matter Physics; Characterization and Evaluation of Materials; Soft and Granular Matter, Complex Fluids and Microfluidics; Physical Chemistry